Where is The Direction Of Physics Education? - Kuswanto Kuswanto (Jurnal Pijar Mipa, 2020)
This article discusses the direction of physics education in the future. This discussion covers physics education, career and technology, and learning to live together and throughout life from a literature study. An extensive study of literature is intended to show the direction of education, especially physics education. The basis of this article is by reviewing research, surveys and online books from several references. Overall, this paper draws conclusions for physics education majors. So the following narratives describe careers that are integrated with technological developments, educational innovations, alternative learning methods/models for physics education.